Evading Big Brother: Using visual methods to understand children's perception of sensors and interest in subverting digital surveillance. (August 2022) - Main, Angus; Yamada-Rice, Dylan
In relation to this Special Issue's focus on ugly information, this article examines children's perception of the often invisible interactions they have with sensor-enabled digital devices and, when prompted, their interest in subverting or blocking these sensors to evade surveillance. The authors report on a study of 12 children, aged 8–12 years, that investigated their knowledge of the sensing abilities of commonly used digital devices (smart phones, smart watches, smart speakers and games consoles), and their attitudes towards having active agency over sensors. In line with this journal's readership, visual methods used for data collection and analysis are described. Specifically, within semi-structured focus groups, drawing was used to understand what children thought was inside digital devices and the extent of their awareness of digital sensors. Child participants were invited to model speculative tools for deceiving digital sensors in order to explore their interest in having agency over digital surveillance. Data in the form of drawings, photographs of models and video recordings were analysed using experimental visual methods that included 3D rendering and comics, as well as visual content and thematic analysis. These drew out four key themes: (1) the role of inference in sensor awareness; (2) misunderstanding of device components and sensing capabilities; (3) attitudes to surveillance; and (4) children's interest in subverting rather than blocking sensors. We discuss how technology companies' desire to create 'magical experiences' may contribute to incorrect inferences about information gathering systems, how this reduces children's agency over the information they share and how it puts them at greater risk from digital surveillance. The article makes an original contribution to knowledge in this area by calling for a two-pronged approach from technology companies and educators to address these issues by making sensor presence more visible, educating children about the full extent of sensor capability and bringing critical discussion of them into curricula.